Evaluation on Accuracy of Snap-On Torque Wrench QD2R200 Calibrated Using ISO 6789:2017 and Stahlwille Standard - Gumelar, Bima Maulana Bagaswara; Parman, Setyamartana; Prasetiyo, Erwan Eko (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
Aviation safety is highly dependent on the accuracy of the tools used, including torque wrenches used in aircraft maintenance. This study evaluated the accuracy of the QD2R200 snap-on torque wrench following the ISO 6789-2017 calibration method using the Stahlwille standard. The study was conducted in the Batam Aero Technic calibration laboratory, with torque wrench measurements at their nominal capacities of 20%, 60%, and 100%. Measurements were repeated five times at each nominal point. The calibration results on the two tools in the laboratory showed that the variation in deviation of the tool with serial number 1016901448 reached ±9%, while the tool with serial number 1116802022 had a deviation of less than ±2%. Testing was carried out in clockwise and counterclockwise directions. The t-test showed a significant difference in results between the two tools, namely p = 0.003. These results emphasize the importance of periodic calibration and show that the ISO 6789:2017 method is effective in measuring torque wrench accuracy, which is important in ensuring safety and reliability in the aviation industry.